Efektivitas Edukasi dan Aplikasi Fluor Topikal terhadap Penurunan Indeks DMF-T - Yuliana Ratna Kumala; Rahmavidyanti Priyanto; Merlya; Nazwa Rizqi Fajrin (Jurnal Pengabdian Masyarakat, 2026)
Dental caries remains a common oral health problem in children and can affect quality of life, growth, and development. Suboptimal dental hygiene habits and limited knowledge of dental care increase the risk of caries from an early age, so sustainable promotive and preventive efforts are needed. This community service activity aims to increase children’s awareness of their oral health and to improve it through education and topical fluoride application at TPQ Darussalam in Malang City. The program was implemented in two activity periods (2024-2025) through stages of coordination with partners, interactive counseling using visual media and toothbrush demonstrations, clinical examination of caries status using DMF-T index, and topical fluoride application by a team of lecturers and dental students. A total of 40 students participated in the 2025 activity. Evaluation was carried out by comparing the results of the DMF-T examination in 2025 with the previous year’s activity data. The examination results showed that the average DMF-T index decreased from 1.69 (2024) to 1.00 (2025), accompanied by increased participation in caries prevention measures. This activity shows that repeated education and community-based topical fluoride interventions are associated with improvements in children’s oral health indicators and can be a model for dental health services in religious education settings